STEVE ROGERS’ CHARACTER IN CAPTAIN AMERICA: THE FIRST AVENGER AS A REPRESENTATION OF HARD WORKING VALUE IN TRADITIONAL AMERICAN VALUES - RAMADHAN, BHAYU (Jurnal Ilmiah Mahasiswa FIB, 2013)
Film is one of the most popular media which often elevates social values of a society. One of American social values is shown in Captain America: The First Avenger. Captain America: The First Avenger clearly portrays Steve Rogers’ character as the representation of the hard working value of the Traditional American Values. In this film, Steve Rogers represents the hard working value by depicting the six characteristics of hard worker. The first characteristic of hard worker that is depicted by Steve Rogers in Captain America: The First Avenger is take initiative. Steve Rogers depicts that he can take initiative when he himself makes a decision to do some tasks. The second characteristic is flexibility. Steve Rogers shows that he is a flexible person because he is able to do another task when he is on the mission without hindering his actual mission. The third characteristic the stamina. Steve Rogers depicts that he has the stamina when he is able to resist the pain and do some actions that need a good physical strength. The fourth characteristic is come up with solution. Rogers can solve problem no matter how difficult it is. The fifth characteristic is preservance. Preservance relates to the quality of a person to finish everything he has started. Steve Rogers is a preservant person when he is able to finish every tasks he started. Rogers will do whatever it takes to finish his tasks. The last characteristics is self-reliance. Steve Rogers relies only to himself in doing his mission.It can be seen that Steve Rogers represents the hard working value of Americans by representing the six characteristics of hard worker. Also it can be concluded that Traditional American Values is a long-lasting value for it remains till today. Key Words: Film, Traditional American Values, Hard Work, Captain America:The First Avenger